2007
DOI: 10.1158/0008-5472.can-07-0771
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Expression of Cysteinyl Leukotriene 2 Receptor in Colorectal Adenocarcinomas Correlates with High Differentiation

Abstract: Increased levels of inflammatory mediators such as cysteinyl leukotrienes (CysLT) have been found in and around tumors. These data, along with our previous observation that the G-protein-coupled receptor CysLT 1 R, which signals survival and proliferation, is up-regulated in colon cancer, suggest an important role for CysLT 1 R in tumor development. The objective of this study was to examine the expression and function of the low-affinity CysLT 2 receptor (CysLT 2 R) in colon cancer. We found lower expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 52 publications
10
56
0
Order By: Relevance
“…19 Several groups have demonstrated the modulation of CysLT receptors by cytokines and inflammatory stimuli. 49,50 Thivierge et al 25 demonstrated that human monocytes express both CysLT1 and CysLT2 receptors similarly and their differentiation in DCs inhibits the expression of CysLT1, whereas their maturation with 200 ng/ml LPS increases CysLTR2 expression. In contrast, upon activation of DCs by LPS (1 lg/ml) no variations in the expression of CysLRT1 were observed but there is a greater reduction of CysLRT2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Several groups have demonstrated the modulation of CysLT receptors by cytokines and inflammatory stimuli. 49,50 Thivierge et al 25 demonstrated that human monocytes express both CysLT1 and CysLT2 receptors similarly and their differentiation in DCs inhibits the expression of CysLT1, whereas their maturation with 200 ng/ml LPS increases CysLTR2 expression. In contrast, upon activation of DCs by LPS (1 lg/ml) no variations in the expression of CysLRT1 were observed but there is a greater reduction of CysLRT2.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been demonstrated in several tissues that the expression of both receptors can be regulated by CysLT release. 18,50 The use of montelukast did not allow us to block the production of IL-23, indicating that it could be modulated by the action of LTC 4 through the CysLTR2. This point could not be evaluated; because there is still no specific receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of the BLT 1 receptor [19] and the CystLT 1 receptor was detected in human colon cancer tissues, whereas CysLT 2 receptor expression was reduced in colon cancer and was associated with poor prognosis, due to its capacity to induce differentiation and growth inhibition [18]. Thus, the CysLT 2 receptor could have more anti-tumorigenic activity than the CysLT 1 receptor in intestinal epithelial cells, and the balance between the two receptors is important for the outcome of tumor progression.…”
Section: Role Of Eicosanoids In the Control Of Intestinal Epithelial mentioning
confidence: 99%
“…With respect to the presence of LT receptors in the intestine, the CysLT 1 receptor is expressed in intestinal epithelial cells and tumorderived intestinal cells [15] whereas the CysLT 2 receptor is expressed in differentiated intestinal epithelial cells but not in tumor-derived intestinal cell lines [18]. The BLT 1 receptor is also expressed in human colon cancer cell lines and colon cancer tissue but not in normal colon tissue [19].…”
mentioning
confidence: 99%
“…Interestingly, an inhibition of either COX or 5-LOX alone resulted in the activation of the other pathway, and consequently, combined treatment with COX and 5-LOX inhibitors produced greater inhibition of tumor cell proliferation. A high expression of the BLT 1 receptor of LTB 4 (Ihara et al, 2007) and the CystLT 1 receptor of LTD 4 was detected in human colon cancer tissues, whereas CysLT 2 receptor expression was reduced in colon cancer and was associated with poor prognosis, due to its capacity to induce differentiation and growth inhibition (Magnusson et al, 2007). Recently, we observed that several LOX metabolites from AA and linoleic acid such as LTB 4 , LTD 4 , 5-HETE, 12-HETE, 15-HETE and 13-hydroxyoctadecanoic acid are involved in the control of CRC cell line proliferation (Cabral et al, 2013;Cabral et al, 2014;Martín-Venegas et al, 2014;Cabral et al, 2015).…”
Section: Role Of the Arachidonic Acid Cascade On Intestinal Epitheliamentioning
confidence: 99%